DIPOR: An IDA-based dynamic proof of retrievability scheme for cloud storage systems. (15th February 2018) - Fu, Anmin; Li, Yuhan; Yu, Shui; Yu, Yan; Zhang, Gongxuan
Abstract: As cloud storage has become more and more ubiquitous, there are a large number of consumers renting cloud storage services. However, as users lose direct control over the data, the integrity and availability of the outsourced data become a big concern for users. Accordingly, how to verify the integrity of stored data and retrieve the availability of the corrupted data has become an urgent problem. Moreover, in most cases, users' data is not always static, but needs to be updated. In this paper, we propose a dynamic proof of retrievability scheme for cloud storage system, named as DIPOR. The DIPOR not only can retrieve the original data of corrupted blocks by using partial healthy data stored in healthy servers, but also support for updating operations of data. Furthermore, the number of forks in our scheme is not fixed, which means we can always look for the optimal forks based on the number of data blocks. In addition, the security analysis indicates that our scheme is provably secure and the performance evaluations show the efficiency of the proposed scheme.